(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper delves into the dynamic interplay between law and morality concerning LGBT issues, examining how societal attitudes and legal frameworks have evolved over time. It explores the historical context of laws governing LGBT rights, highlighting pivotal moments and landmark cases that have shaped the trajectory of legal and moral discourse. Through a comprehensive analysis, this study elucidates the complexities of navigating the intersection of law and morality in the context of LGBT rights, shedding light on the ongoing evolution of societal norms and legal principles.